Ten years of survival among early-stage breast cancer patients: a hospital-based study - Nahar, Shamsun; Jamal Uddin; Saidul Haque; Nazir Uddin Mollah; Sarwar Alam; M. A. Bari; Faruk Ahmed; Khursheda Akhtar; Mahmudur Rahman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The incidence rate of breast cancer is gradually increasing all over the world. In Bangladesh, we have very little research-based information regarding the survival of patients with early-stage breast cancer. The aim of this study was to determine the survival outcome of early-stage (Stages I- IIIA) breast cancer among female patients in respect to their age group, stage of the disease, tumor grade, nodal status, and hormone receptor status Methods: This was a prospective observational study focused on the survival outcome conducted in the department of clinical oncology, Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka, Bangladesh during the period from December 2011 to December 2021. One hundred and five (105) female patients with early-stage (Stages I-IIIA) breast cancer were selected following the inclusion and exclusion criteria as the study subjects. Properly informed written consent was taken from all the participants before starting data collection. All data were processed, analyzed, and disseminated by MS office and SPSS programs as per need. Results: The survival rate was found 79% (n=83). We observed stage-wise 10-year overall survival among the participants where 51.60%, 36.10%, and 12.30% survived from tumor stage I, II, and III respectively. We also observed that 29%, 60% and 11% of patients had survived from tumor grade I, II, and III respectively (Out of 83 survival cases). On the other hand, among the 83 10-year survival patients, 53.8% were of negative nodal status whereas 34.20% were of positive nodal status patients. Among the survived 83 patients, 86% were from >40 years’ age group whereas the rest 14% were from <40 years of age group. Conclusions: Early detection and treatment of breast cancer provide a definitive survival benefit. The results of the study showed that comprehensive screening and early detection of breast cancer is required to improve the survival outcome.